Influence of delta-6-desaturase on hepatic membrane composition in obesity/insulin resistance: implications for the development of cardiometabolic syndrome - Nemr, Dina Ahmed Safwat (AUC Knowledge Fountain, 2013)
Obesity has become a worldwide phenomenon and has been accompanied by a parallel rise in the incidence of insulin resistance, type 2 diabetes, inflammation, dyslipidemia and cardiovascular disease. Together, these symptoms have been collectively referred to as “cardiometabolic disease" (CMD). Delta-6-desaturase catalyzes the rate limiting step in the conversion of linoleic acid (LA) into arachidonic acid (AA), which in turn is converted into pro-inflammatory eicosanoids. Increasing evidence suggests a link between D6D hyperactivity and the development of CMD, though this hypothesis remains to be tested experimentally. We hypothesized that obesity and a high-fat diet, leading to the development of CMD, will be reversed/prevented by the pharmacological inhibition of D6D using the drug SC-26196. In mouse models of obesity resulting from leptin-deficiency (ob/ob) or a high-fat diet (in LDL receptor knockout mice) a detailed assessment of the acyl composition of serum and hepatic phospholipids was conducted to provide insight into the nature of phospholipid remodeling in disease and with D6D inhibition, as well as the potential interaction of D6D with phosphatidylethanolamine N-methyltransferase (PEMT), the enzyme which catalyzes the hepatic conversion of phosphatidylethanolamine (PE) into phosphatidylcholine (PC). The hepatic PC/PE ratio was used as a surrogate measure for PEMT activity. The extent of CMD was assessed by analyses of serum triglycerides, cholesterol, and macrophage chemoattractant protein-1, as well as hepatic free AA and eicosanoids. Obesity and a high-fat diet resulted in elevated D6D activity, accompanied by manifestations of CMD, which were reversed with D6D inhibition. Though the mechanism of the interaction between D6D and PEMT remains unclear, the results suggest that it may be bidirectional, where D6D may influence PEMT activity, in addition to the reported effects of PEMT on D6D. Differences were observed between the ob/ob and LDLR-/- models in disease etiology, pathophysiology, and response to treatment. These differences should be considered when selecting a research model of CMD. In conclusion, the production of AA through D6D metabolism and the potential involvement of PEMT and other enzymes, such as PLA-2, appear to play an important role in the pathogenesis of CMD by complex interactions with multiple systems that merit further investigation.